Solid state battery

By using polyisobutylene with different viscosity average molecular weights as binder in the electrodes of solid-state batteries, the internal stress problem caused by changes in material volume during charging and discharging of solid-state batteries is solved, effectively protecting the conductive network in the electrode space, and cycling performance of solid-state batteries is improved.

CN119890402APending Publication Date: 2025-04-25EVE ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411823533.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

During the charging and discharging process, solid-state batteries cause internal stress caused by changes in material volume, resulting in damage to the spatial conductive network.

Method used

A binder is introduced into the electrode of a solid-state battery. The binder consists of first polyisobutylene and second polyisobutylene with different viscosity average molecular weights. It has the characteristics of good viscosity and poor film formation. It can exist in granular form and buffer the stress caused by volume changes during charging and discharging of the electrode material.

Benefits of technology

By introducing such a binder, the degree of damage to the conductive network in the inner space of the electrode can be effectively alleviated and the circulation and electrochemical performance of solid-state batteries can be improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890402A_ABST
    Figure CN119890402A_ABST
Patent Text Reader

Abstract

The invention provides a solid-state battery which comprises an electrode, the electrode comprises a current collector and an active material layer combined with the current collector, the active material layer comprises an active material and a binder, the binder comprises polyisobutene, and the polyisobutene comprises first polyisobutene and second polyisobutene, the viscosity average molecular weight of the first polyisobutylene is less than the viscosity average molecular weight of the second polyisobutylene. The binder used in the electrode of the solid-state battery comprises the first polyisobutene and the second polyisobutene which are different in viscosity-average molecular weight, and the first polyisobutene and the second polyisobutene are matched with each other, so that the binder has the characteristics of good viscosity and poor film-forming property, and the binder can exist in the active material layer in a granular form; and the stress caused by volume change of an active material in the electrode in the charging and discharging process is better buffered by virtue of the viscosity and elasticity of the polymer, so that the damage degree of a conductive network in the internal space of the electrode is relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solid-state batteries, and in particular to a solid-state battery. Background Art

[0002] During the operation of solid-state batteries, the expansion mismatch of internal materials will cause serious internal stress problems. In solid-state batteries, the sources of internal stress mainly include the following three aspects: 1. Thermal expansion caused by temperature changes. Due to the different thermal expansion coefficients between the internal materials of solid-state batteries, temperature changes will cause stress inside the solid-state battery, especially in the case of rapid temperature changes, due to the uneven thermal expansion of the material, it will cause large mechanical stress. 2. Volume changes of electrode materials (including positive and negative materials) caused by cyclic charging and discharging. During the charging and discharging process of solid-state batteries, the volume changes of positive and negative electrode materials caused by electrochemical reactions will cause the accumulation of internal stress of solid-state batteries. The magnitude of this stress is related to factors such as the charging and discharging rate and the number of cycles. 3. The effect of external stress. In practical applications, solid-state batteries are often subjected to pressure or tension from the external environment. This external stress will directly act on the positive and negative electrode materials and electrolyte layers of the solid-state battery, resulting in the generation of mechanical stress. Among them, the volume change of electrode materials, especially active materials during lithium ion insertion / extraction, is the main source of internal stress of solid-state batteries. The internal stress of solid-state batteries will destroy the internal space conductive network of solid-state batteries and cause contact loss. Summary of the invention

[0003] An embodiment of the present application provides a solid-state battery that can alleviate the technical problem that the internal stress of the solid-state battery causes damage to the spatial conductive network.

[0004] In a first aspect, an embodiment of the present application provides a solid-state battery, comprising an electrode, wherein the electrode comprises a current collector and an active material layer combined with the current collector, wherein the active material layer comprises an active material and a binder, wherein the binder comprises polyisobutylene, and the polyisobutylene comprises a first polyisobutylene and a second polyisobutylene, wherein the viscosity-average molecular weight of the first polyisobutylene is less than the viscosity-average molecular weight of the second polyisobutylene.

[0005] In one embodiment, the viscosity average molecular weight of the polyisobutylene is 40,000-2,600,000.

[0006] In one embodiment, the viscosity average molecular weight of the first polyisobutylene is 40,000-85,000, and the viscosity average molecular weight of the second polyisobutylene is 425,000-2,600,000.

[0007] In one embodiment, the difference between the viscosity average molecular weight of the second polyisobutylene and the viscosity average molecular weight of the first polyisobutylene is greater than or equal to 340,000.

[0008] In one embodiment, the ratio of the viscosity average molecular weight of the second polyisobutylene to the viscosity average molecular weight of the first polyisobutylene is 5-65.

[0009] In one embodiment, in the binder, the content of the first polyisobutylene is 30 wt % to 80 wt %, and the content of the second polyisobutylene is 20 wt % to 70 wt %.

[0010] In one embodiment, in the active material layer, the content of the binder is 0.5 wt % to 5 wt %.

[0011] In one embodiment, the active material layer further includes a solid electrolyte.

[0012] In one embodiment, in the active material layer, the content of the active material is 70wt% to 94wt%, or the content of the conductive agent is 0.5wt% to 5wt%, or the content of the solid electrolyte is 5wt% to 20wt%.

[0013] In one embodiment, the active material includes at least one of a positive electrode active material and a negative electrode active material.

[0014] In one embodiment, the positive electrode active material includes at least one of lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium iron manganese phosphate and lithium-rich manganese-based positive electrode materials; and / or, the negative electrode active material includes at least one of graphite, silicon, silicon carbon and lithium titanate.

[0015] In one embodiment, the solid electrolyte includes at least one of a sulfide electrolyte, a halide electrolyte, an oxide electrolyte, and a polymer electrolyte.

[0016] In one embodiment, the active material layer further includes a conductive agent, and the conductive agent includes at least one of carbon black, conductive graphite, carbon nanotubes and nano-carbon fibers.

[0017] Beneficial effects of the embodiments of the present application:

[0018] The solid-state battery provided in the embodiment of the present application uses a binder in the electrode to bond the active material to the current collector and form an active material layer. The binder includes a first polyisobutylene and a second polyisobutylene with different viscosity-average molecular weights. The two cooperate with each other to make the binder have the characteristics of good viscosity and poor film-forming properties. In this way, the binder can exist in a granular form in the active material layer, and better use the viscosity and elasticity of its own polymer to buffer the stress caused by the volume change of the active material in the electrode during the charging and discharging process, thereby alleviating the degree of damage to the conductive network in the internal space of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0020] Figure 1 is a schematic cross-sectional structure diagram of a solid-state battery provided in an embodiment of the present application;

[0021] Figure 2 It is a schematic diagram of the cross-sectional structure of the electrode provided in the embodiment of the present application. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0023] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.

[0024] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0025] In the present application, "at least one" means one or more, and "plurality" means two or more. "One or several", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0026] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0027] In response to the problem that the internal stress of solid-state batteries will destroy the internal space conductive network of solid-state batteries and cause contact loss, the embodiments of the present application start from the perspective of regulating electrode components. By introducing a binder into the electrode of the solid-state battery, the binder includes polyisobutylene with different viscosity-average molecular weights, which has the characteristics of good viscosity and poor film-forming properties. In this way, the binder exists in a granular form inside the electrode, and can better use the viscosity and elasticity of its own polymer to buffer the stress caused by the volume change of the electrode material during the charging and discharging process, thereby alleviating the degree of damage to the internal space conductive network of the solid-state battery.

[0028] Specifically, see Figure 1 and Figure 2 The embodiment of the present application provides a solid-state battery 10, which includes an electrode 1, wherein the electrode 1 includes a current collector 11 and an active material layer 12 combined with the current collector 11. The active material layer 12 includes an active material and a binder. The binder includes polyisobutylene, and the polyisobutylene includes a first polyisobutylene and a second polyisobutylene, wherein the viscosity average molecular weight of the first polyisobutylene is less than the viscosity average molecular weight of the second polyisobutylene.

[0029] Here, the electrode 1 is also referred to as an electrode sheet, and the electrode 1 may be a positive electrode sheet 101 or a negative electrode sheet 102. The electrode 1 includes a current collector 11 and an active material layer 12, and the active material layer 12 is combined with the current collector 11. As an example, the active material layer 12 is bonded to one side of the current collector 11, or the active material layer 12 is bonded to both opposite sides of the current collector 11. It can be understood that the active material includes at least one of a negative electrode active material and a positive electrode active material.

[0030] As an example, the electrode 1 is a positive electrode sheet 101, the current collector 11 is a positive electrode current collector, and the active material layer 12 includes a positive electrode active material. As an example, the positive electrode current collector includes aluminum foil. Optionally, the positive electrode active material includes at least one of lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, and lithium-rich manganese-based positive electrode materials.

[0031] As an example, the electrode 1 is a negative electrode sheet 102, the current collector 11 is a negative electrode current collector, and the active material layer 12 includes a negative electrode active material. As an example, the negative electrode current collector includes copper foil. Optionally, the negative electrode active material includes at least one of graphite, silicon, silicon carbon and lithium titanate.

[0032] In order to combine the active material with the current collector 11, the viscosity of the binder is usually required. Viscosity is caused by the interaction between molecules inside the material, mainly including cohesion and viscosity. Cohesion refers to the attraction between molecules, while viscosity refers to the friction between molecules. These forces interact to form the viscosity of the material.

[0033] Polyisobutylene (PIB) is a saturated linear polymer with good adhesion. The molecular weight has a significant effect on the adhesion of polyisobutylene. Polyisobutylene with different molecular weights exhibits different adhesion effects. Generally, the smaller the molecular weight, the better the fluidity of polyisobutylene; the higher the molecular weight, the better the cohesion and toughness of polyisobutylene.

[0034] The first polyisobutylene and the second polyisobutylene are polyisobutylenes having different viscosity average molecular weights. The viscosity average molecular weight of the first polyisobutylene is less than that of the second polyisobutylene, that is, the fluidity of the first polyisobutylene is better than that of the second polyisobutylene, and the cohesion and toughness of the second polyisobutylene are better than those of the first polyisobutylene. Here, the first polyisobutylene may be a polyisobutylene having a viscosity average molecular weight of a specified value or within a specified range, and similarly, the second polyisobutylene may be a polyisobutylene having a viscosity average molecular weight of a specified value or within a specified range.

[0035] The viscosity average molecular weight here refers to the molecular weight of the polymer measured by the dilute solution viscosity method, also known as the viscosity average molecular weight. The process of determining the viscosity average molecular weight of the polymer by the dilute solution viscosity method includes:

[0036] Dissolve the polymer sample in a suitable solvent to prepare a solution of a certain concentration;

[0037] The relative viscosity (ηr) was obtained by measuring the efflux time of the solution and the pure solvent at the same temperature using an Ubbelohde viscometer;

[0038] The intrinsic viscosity (η) is obtained by extrapolation, that is, by plotting ln(ηr / C) versus C, and extrapolating to C=0 to obtain the intercept, which is the intrinsic viscosity (η);

[0039] The viscosity average molecular weight Mη is calculated using the Mark-Houwink equation. The equation is usually in the form of [η] = K × M^α, where K and α are constants related to the polymer, solvent, and temperature. These constants can be obtained through experiments or by consulting relevant literature.

[0040] It can be understood that the smaller the viscosity average molecular weight of the polymer, the shorter the molecular chain of the polymer; the larger the viscosity average molecular weight of the polymer, the longer the molecular chain of the polymer, so that the molecular chain of the polymer is more likely to bend and entangle, thereby increasing the gap between the polymers. By mixing the first polyisobutylene and the second polyisobutylene with different viscosity average molecular weights, the molecular chain of the first polyisobutylene with a smaller viscosity average molecular weight can be filled in the gap between the molecular chain of the second polyisobutylene with a larger viscosity average molecular weight and entangled with the molecular chain of the second polyisobutylene, which is conducive to improving the viscosity between the polymer molecules, thereby improving the adhesion of the binder, and in this way, the binder is not easy to form a film in the active material layer 12 of the electrode 1, and the binder can be distributed in the active material layer 12 in a granular form, such as a spherical or quasi-spherical shape, and the granular binder can not only effectively relieve stress, but also reduce the adverse effects on ion transmission.

[0041] The solid-state battery 10 provided in the embodiment of the present application uses a binder in the electrode 1 to bond the active material to the current collector 11 and form an active material layer 12. The binder includes a first polyisobutylene and a second polyisobutylene with different viscosity-average molecular weights. The two cooperate with each other to make the binder have the characteristics of good viscosity and poor film-forming properties. In this way, the binder can exist in the active material layer 12 in a granular form, and better use the viscosity and elasticity of its own polymer to buffer the stress caused by the volume change of the active material in the electrode 1 during the charging and discharging process, thereby alleviating the degree of damage to the conductive network in the internal space of the electrode 1.

[0042] It can be understood that in the solid-state battery 10 provided in the embodiment of the present application, polyisobutylene with different viscosity-average molecular weights is introduced into the electrode 1. The polyisobutylene not only serves as a binder, but also acts as an elastomer. While maintaining the good bonding ability of the electrode 1, it can absorb the mechanical stress during the charging and discharging process and play a role of buffer protection.

[0043] In some embodiments, the viscosity average molecular weight of polyisobutylene is 40,000 to 2,600,000. If the viscosity average molecular weight of polyisobutylene is too small or too large, it will affect the bonding ability and buffering capacity of the adhesive. Generally, the smaller the viscosity average molecular weight of polyisobutylene, the lower the cohesion of polyisobutylene and the insufficient viscosity. The larger the viscosity average molecular weight of polyisobutylene, the larger the elastic modulus of polyisobutylene. As an example, the viscosity average molecular weight of polyisobutylene is 40,000, 60,000, 80,000, 100,000, 200,000, 500,000, 800,000, 1,000,000, 1,500,000, 2,000,000, 2,500,000 or 2,600,000.

[0044] In some embodiments, the viscosity average molecular weight of the first polyisobutylene is 40,000 to 85,000, and the viscosity average molecular weight of the second polyisobutylene is 425,000 to 2,600,000. Generally, the viscosity average molecular weight of the first polyisobutylene should not be too small, otherwise the fluidity of the first polyisobutylene will increase, which will not only reduce the viscosity of the adhesive, but also make the adhesive easy to form a film when used; although the increase in the viscosity average molecular weight of the second polyisobutylene can make the adhesive less likely to form a film when used, the viscosity average molecular weight of the second polyisobutylene should not be too large, otherwise the elastic modulus of the adhesive will be relatively high after curing, which will affect the cushioning performance. If the viscosity average molecular weight of the first polyisobutylene is too large, or the viscosity average molecular weight of the second polyisobutylene is too small, it will be unfavorable for the coordination between the molecular chains of the first polyisobutylene and the second polyisobutylene, thereby affecting the improvement of the viscosity of the adhesive. By controlling the viscosity-average molecular weights of the first polyisobutylene and the second polyisobutylene respectively within the above ranges, the fluidity of the first polyisobutylene and the cohesive force of the second polyisobutylene are maintained at an appropriate level, and when the first polyisobutylene is mixed with the second polyisobutylene, the fluidity of the first polyisobutylene and the chain length of the first polyisobutylene enable the molecular chain of the first polyisobutylene to better match the molecular chain of the second polyisobutylene, so that the first polyisobutylene can better fill the gaps in the second polyisobutylene and entangle with the second polyisobutylene, achieving better performance complementarity, thereby making the adhesive have good adhesion but poor film-forming properties, and further making the adhesive have both better bonding ability and buffering capacity. As an example, the viscosity average molecular weight of the first polyisobutylene is 40,000, 50,000, 60,000, 65,000, 70,000, 75,000, 80,000 or 85,000, and the viscosity average molecular weight of the second polyisobutylene is 425,000, 500,000, 600,000, 700,000, 800,000, 900,000, 1000,000, 1200,000, 1400,000, 1600,000, 1800,000, 2000,000, 2200,000, 2400,000 or 2600,000.

[0045] In some embodiments, the difference between the viscosity average molecular weight of the second polyisobutylene and the viscosity average molecular weight of the first polyisobutylene is greater than or equal to 340,000. It can be understood that the smaller the difference between the viscosity average molecular weight of the second polyisobutylene and the viscosity average molecular weight of the first polyisobutylene, the closer the chain lengths of the two are, so that the difficulty of matching between the molecular chain of the second polyisobutylene and the molecular chain of the first polyisobutylene increases. Therefore, by increasing the difference between the viscosity average molecular weight of the second polyisobutylene and the first polyisobutylene, it is beneficial to promote the molecular chain-level matching effect of the second polyisobutylene and the first polyisobutylene after mixing, so that the adhesive can have both viscosity and elasticity. As an example, the difference between the viscosity average molecular weight of the second polyisobutylene and the viscosity average molecular weight of the first polyisobutylene is 340,000, 400,000, 500,000, 800,000, 1,000,000, 2,000,000, 2,500,000 or 2,560,000. In some embodiments, the ratio of the viscosity average molecular weight of the second polyisobutylene to the viscosity average molecular weight of the first polyisobutylene is 5 to 56. It can be understood that the smaller the ratio of the viscosity average molecular weight of the second polyisobutylene to the viscosity average molecular weight of the first polyisobutylene, the closer the viscosity average molecular weight of the second polyisobutylene is to the viscosity average molecular weight of the first polyisobutylene, and the closer the molecular chain lengths of the two are, so that the difficulty of the molecular chain of the first polyisobutylene entering the gaps of the molecular chain of the second polyisobutylene will increase; and the larger the ratio of the viscosity average molecular weight of the second polyisobutylene to the viscosity average molecular weight of the first polyisobutylene, the greater the difference between the viscosity average molecular weight of the second polyisobutylene and the viscosity average molecular weight of the first polyisobutylene, so that the molecular chain lengths of the two are also different, although the difficulty of the molecular chain of the first polyisobutylene entering the gaps of the molecular chain of the second polyisobutylene is reduced, the molecular chain of the first polyisobutylene is not easy to be entangled with the molecular chain of the second polyisobutylene, thereby affecting the stability of the coordination of the two. Therefore, by controlling the ratio of the viscosity average molecular weight of the second polyisobutylene to the viscosity average molecular weight of the first polyisobutylene within this range, the second polyisobutylene and the first polyisobutylene can be promoted to produce a stable coordination effect at the molecular chain level after mixing, so that the adhesive has better viscosity and elasticity. As an example, the ratio of the viscosity average molecular weight of the second polyisobutylene to the viscosity average molecular weight of the first polyisobutylene is 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55 or 56.

[0046] In some embodiments, in the adhesive, the content of the first polyisobutylene is 30wt% to 80wt%, and the content of the second polyisobutylene is 20wt% to 70wt%. In the adhesive, the content of the first polyisobutylene should not be too small, otherwise the elastic modulus of the adhesive will increase, and if the content of the first polyisobutylene is too large, the cohesion of the adhesive will be insufficient, which will reduce the viscosity of the adhesive; the content of the second polyisobutylene should not be too small, otherwise the adhesive will easily form a film, but if the content of the second polyisobutylene is too large, the elastic modulus of the adhesive will increase. By controlling the ratio of the first polyisobutylene to the second polyisobutylene within the above range, the adhesive can have both better bonding ability and buffering ability. As an example, the content of the first polyisobutylene is 30 wt%, 40 wt%, 50 wt%, 60 wt%, 70 wt% or 80 wt%, and the content of the second polyisobutylene is 20 wt%, 30 wt%, 40 wt%, 50 wt%, 60 wt% or 70 wt%.

[0047] In some embodiments, the active material layer 12 further includes a conductive agent. By adding the conductive agent, the conductivity of the active material layer 12 is improved and the internal resistance of the solid-state battery 10 is reduced. As an example, the conductive agent includes at least one of carbon black, conductive graphite, carbon nanotubes, and nano-carbon fibers.

[0048] In some embodiments, the content of the binder in the active material layer 12 is 0.5wt% to 5wt%. Too low a content of the binder in the active material layer 12 will not only affect the bonding effect between the active material layer 12 and the current collector 11 and the strength of the active material layer 12 itself, but will also reduce the ability of the electrode 1 to buffer stress; however, the binder itself contributes very little to the battery energy density; of course, the content of the binder should not be too large, as too much of the binder content will also affect ion transport in the electrode 1. Optionally, the content of the binder in the active material layer 12 is 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt% or 5wt%. In addition, by controlling the content of the binder to be within the range of 0.5wt% to 5wt%, the bonding requirements of the electrode 1 can be basically met without the need to introduce other bonding materials.

[0049] In some embodiments, the active material layer 12 further includes a solid electrolyte. In the case of a solid-state battery 10, such as an all-solid-state battery, the active material layer 12 further includes a solid electrolyte.

[0050] When the solid-state battery 10 is an all-solid-state battery, a solid electrolyte membrane 2 is used in the solid-state battery 10 to replace the electrolyte in the liquid battery, so that the electrode 1 in the solid-state battery 10 is difficult to be infiltrated by the electrolyte like the electrode in the liquid battery to achieve solid-liquid contact conduction, so the solid electrolyte can be added to the active material layer 12 to achieve solid-solid contact conduction. Under the condition that only the solid electrolyte exists inside the electrode 1, the transmission of lithium ions can only be achieved through the solid-solid contact between the active material and the solid electrolyte. However, the active material will be accompanied by a change in volume during charging and discharging, thereby causing poor solid-solid contact inside the electrode 1 and hindering the transmission of lithium ions. The embodiment of the present application introduces the above-mentioned composite adhesive, which has good elasticity and strain resistance, can buffer the volume change of the material inside the electrode 1, and achieve stable lithium ion transmission. Optionally, the solid electrolyte includes at least one of a sulfide electrolyte, a halide electrolyte, an oxide electrolyte and a polymer electrolyte. As an example, the sulfide electrolyte includes at least one of lithium phosphorus sulfur chlorine (LPSCl), lithium germanium phosphorus sulfur (LGPS) and its derivatives. As an example, the halide electrolyte includes at least one of Li3YCl6, Li3InCl6 and derivatives thereof. As an example, the oxide electrolyte includes at least one of lithium lanthanum zirconium oxide (LLZO), lithium aluminum titanium phosphate (LATP), lithium lanthanum titanate (LLTO) and derivatives thereof.

[0051] In some embodiments, the solid-state battery 10 may also be a semi-solid-state battery. A semi-solid-state battery refers to a battery in which the electrode 1 on either side does not contain a liquid electrolyte, and the electrode 1 on the other side contains a liquid electrolyte, or the mass or volume of the solid electrolyte in the battery cell accounts for more than half of the total mass or volume of the electrolyte in the battery cell.

[0052] In some embodiments, solid-state battery 10 comprises a lithium-ion battery.

[0053] In some embodiments, in the active material layer 12, the content of the binder is 0.5 wt% to 5 wt%, the content of the active material is 70 wt% to 94 wt%, the content of the conductive agent is 0.5 wt% to 5 wt%, and the content of the solid electrolyte is 5 wt% to 20 wt%. As an example, in the active material layer 12, the content of the binder is 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt% or 5wt%; the content of the active material is 70wt%, 72wt%, 75wt%, 78wt%, 80wt%, 82wt%, 84wt%, 85wt%, 87wt%, 89wt%, 90wt%, 91wt%, 92wt%, 93wt% or 94wt%; the content of the conductive agent is 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt% or 5wt%; the content of the solid electrolyte is 5wt%, 8wt%, 10wt%, 12wt%, 15wt%, 18wt% or 20wt%.

[0054] In some embodiments, the solid-state battery 10 further includes a solid electrolyte membrane 2, the electrode 1 includes a positive electrode sheet 10 and a negative electrode sheet 102, the positive electrode sheet 10 and the negative electrode sheet 102 are respectively arranged on opposite sides of the solid electrolyte membrane 2, and the solid electrolyte membrane 2 is located between the positive electrode sheet 10 and the negative electrode sheet 102. At least one of the positive electrode sheet 10 and the negative electrode sheet 102 is configured to include a current collector 11 and an active material layer 12. As an example, the positive electrode sheet 10 includes a current collector 11 and an active material layer 12, and the negative electrode is a lithium metal negative electrode.

[0055] In some embodiments, the solid electrolyte in the solid electrolyte membrane 2 includes at least one of a sulfide electrolyte, a halide electrolyte, an oxide electrolyte, and a polymer electrolyte. Optionally, the solid electrolyte included in the solid electrolyte membrane 2 is the same as the solid electrolyte included in the active material layer 12.

[0056] In some embodiments, the preparation method of electrode 1 includes:

[0057] S1, adding a binder into a solvent and dissolving it to obtain a bonding glue solution;

[0058] S2, performing a first mixing process on the active material and the conductive agent to obtain an electrode mixture;

[0059] S3, performing a second mixing process on the bonding glue and the electrode mixture to obtain an electrode slurry;

[0060] S4, performing film-forming treatment on the electrode slurry on the current collector to obtain a wet film layer;

[0061] S5, drying the wet film layer to obtain the electrode 1.

[0062] The preparation method is simple and easy to implement.

[0063] In some embodiments, the solvent includes p-xylene. As an example, step S1 includes: adding a binder (i.e., polyisobutylene) to a p-xylene solvent from which water has been removed, and stirring for 20 to 72 hours to completely dissolve the polyisobutylene in the p-xylene to form a bonding adhesive. Here, the bonding adhesive refers to a colloidal solution containing a binder.

[0064] In more detail, the preparation process of the bonding adhesive includes: dissolving two polyisobutylenes with different molecular weights in a paraxylene solvent respectively, the adhesive of the small molecular weight polyisobutylene is recorded as A adhesive, and the adhesive of the large molecular weight polyisobutylene is recorded as B adhesive; according to the ratio, add A adhesive and B adhesive to the paraxylene solvent, and stir magnetically for 20 hours to 72 hours.

[0065] In some embodiments, the first mixing process includes a shearing process. As an example, step S2 includes: weighing the active material, the solid electrolyte and the conductive agent in proportion, adding the three into a high-speed mixer, and mixing the three uniformly by high-energy shearing to obtain an electrode mixture.

[0066] In some embodiments, the solid content of the electrode slurry is 50wt% to 70wt%. As an example, the solid content of the electrode slurry is 50wt%, 55wt%, 60wt%, 65wt% or 70wt%. The solid content of the electrode slurry refers to the proportion of all substances in the electrode slurry except the solvent in the electrode slurry. Optionally, in all other substances in the electrode slurry except the solvent, the content of polyisobutylene is 0.5wt% to 5wt%, such as 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt% or 5wt%. Optionally, in all other substances in the electrode slurry except the solvent, the total content of active materials, solid electrolytes and conductive agents is 95wt% to 99.5wt%, such as 95wt%, 96wt%, 97wt%, 98wt%, 99wt% or 99.5wt%. Optionally, among all substances other than the solvent in the electrode slurry, the content of polyisobutylene is 0.5wt% to 5wt%, the content of active material is 70wt% to 94wt%, the content of conductive agent is 0.5wt% to 5wt%, and the content of solid electrolyte is 5wt% to 20wt%.

[0067] In some embodiments, the second mixing process includes a stirring process. As an example, step S3 includes: adding a bonding glue to the electrode mixture, and using a double star type mixer to quickly stir and disperse. Optionally, an appropriate amount of solvent can be further added during the preparation of the electrode slurry to improve the dispersion effect of the material and adjust the solid content of the electrode slurry.

[0068] In some embodiments, the film forming process includes a coating process. Optionally, the coating method includes but is not limited to at least one of gravure coating, micro-gravure coating, spraying and electrostatic spinning technology. As an example, step S4 includes: coating the electrode slurry on the surface of the current collector, such as a metal foil, to obtain a wet film layer, which refers to a film layer containing a solvent.

[0069] In some embodiments, the drying process includes a heating process. Optionally, the temperature of the heating process is 40°C to 90°C, and the time is 2h to 15h. As an example, step S5 includes: vacuum drying the wet film layer at 45°C for 2h, and then vacuum drying it at 80°C for 12h. Optionally, step S5 also includes a roller pressing process, in which the roller gap is 10μm to 30μm, the roller temperature is 25°C to 55°C, and the roller speed is 1rpm to 5rpm. As an example, the roller gap is 10μm, 15μm, 20μm, 25μm or 30μm; the roller temperature is 25°C, 30°C, 35°C, 40°C, 45°C, 50°C or 55°C; the roller speed is 1rpm, 2rpm, 3rpm, 4rpm or 5rpm.

[0070] The following describes it in detail with reference to specific embodiments.

[0071] Example 1

[0072] S01, preparation of PIB glue: take a first polyisobutylene with a viscosity average molecular weight of 40,000 and add it to a dehydrated p-xylene solvent, stir at room temperature to completely dissolve the first polyisobutylene in the p-xylene, and form a uniform and stable PIB glue A; take a second polyisobutylene with a viscosity average molecular weight of 425,000 and add it to a dehydrated p-xylene solvent, stir at room temperature to completely dissolve the second polyisobutylene in the p-xylene, and form a uniform and stable PIB glue B; add PIB glue A and PIB glue B to the p-xylene solvent according to the content ratio, stir magnetically for 24 hours, and obtain PIB glue, the mass ratio of the first polyisobutylene to the second polyisobutylene in the PIB glue is 4:6, that is, the mass content of the first polyisobutylene in the binder is 40%, and the mass content of the second polyisobutylene in the binder is 60%. The PIB glue is colorless and transparent without obvious bubbles.

[0073] S02. Premixing of electrode materials: Weigh the electrode materials according to the mass ratio of active material (high nickel ternary positive electrode material), solid electrolyte (lithium phosphorus sulfur chlorine, referred to as LPSCl), and conductive agent (vapor-grown carbon fiber, referred to as VGCF) = 83.5:10:5. Add the above materials into a high-speed mixer, mix the above materials evenly through high-energy shearing, and obtain a positive electrode mixed material.

[0074] S03, slurry preparation: add the PIB glue prepared in step S01 to the positive electrode mixed material uniformly mixed in step S02, use a double star type mixer to quickly stir and disperse, and gradually add an appropriate amount of p-xylene solvent to form a uniform and stable slurry. This step controls the solid content in the final slurry to be 60wt%, and the total amount of the first polyisobutylene and the second polyisobutylene accounts for 1.5wt% of the total mass of all solids. All solids refer to other substances in the slurry except the solvent p-xylene. Here, the first polyisobutylene and the second polyisobutylene are used as binders together.

[0075] S04, pole piece coating: the slurry prepared in step S03 is evenly coated on the surface of the aluminum foil, and vacuum dried at 45°C for 2h and 80°C for 12h to fully remove the p-xylene solvent to obtain a pole piece, specifically a positive pole piece.

[0076] S05, making a battery cell: laminating, packaging, isostatic pressing and other steps are performed on the above-mentioned positive electrode sheet, Li metal negative electrode and solid electrolyte membrane to obtain an all-solid-state battery. The solid electrolyte membrane comprises 95wt% lithium phosphorus sulfur chloride (LPSCl) and 5wt% polyisobutylene.

[0077] Example 2

[0078] The difference from Example 1 is that the viscosity average molecular weight of the second polyisobutylene in step S01 is 800,000.

[0079] Example 3

[0080] The difference from Example 1 is that the viscosity average molecular weight of the second polyisobutylene in step S01 is 1,100,000.

[0081] Example 4

[0082] The difference from Example 1 is that the viscosity average molecular weight of the second polyisobutylene in step S01 is 2,600,000.

[0083] Example 5

[0084] The difference from Example 4 is that in step S01, the mass ratio of the first polyisobutylene to the second polyisobutylene in the PIB adhesive is 8:2, that is, the mass content of the first polyisobutylene in the adhesive is 80%, and the mass content of the second polyisobutylene in the adhesive is 20%.

[0085] Example 6

[0086] The difference from Example 1 is that in step S01, the viscosity average molecular weight of the first polyisobutylene is 55,000.

[0087] Example 7

[0088] The difference from Example 6 is that in step S01, the viscosity average molecular weight of the second polyisobutylene is 800,000.

[0089] Example 8

[0090] The difference from Example 6 is that in step S01, the viscosity average molecular weight of the second polyisobutylene is 1,100,000.

[0091] Example 9

[0092] The difference from Example 6 is that in step S01, the viscosity average molecular weight of the second polyisobutylene is 2,600,000.

[0093] Example 10

[0094] The difference from Example 8 is that in step S01, the mass ratio of the first polyisobutylene to the second polyisobutylene in the PIB adhesive is 6:4, that is, the mass content of the first polyisobutylene in the adhesive is 60%, and the mass content of the second polyisobutylene in the adhesive is 40%.

[0095] Embodiment 11

[0096] The difference from Example 1 is that in step S01, the viscosity average molecular weight of the first polyisobutylene is 73,000.

[0097] Example 12

[0098] The difference from Example 11 is that in step S01, the viscosity-average molecular weight of the second polyisobutylene is 800,000.

[0099] Embodiment 13

[0100] The difference from Example 11 is that in step S01, the viscosity average molecular weight of the second polyisobutylene is 1,100,000.

[0101] Embodiment 14

[0102] The difference from Example 11 is that in step S01, the viscosity average molecular weight of the second polyisobutylene is 2,600,000.

[0103] Embodiment 15

[0104] The difference from Example 11 is that in step S01, the mass ratio of the first polyisobutylene to the second polyisobutylene in the PIB adhesive is 5:5, that is, the mass content of the first polyisobutylene in the adhesive is 50%, and the mass content of the second polyisobutylene in the adhesive is 50%.

[0105] Example 16

[0106] The difference from Example 11 is that in step S03, the total amount of the first polyisobutylene and the second polyisobutylene accounts for 2.5 wt % of the total mass of all solids.

[0107] Comparative Example 1

[0108] The difference from Example 11 is that in step S01, HNBR (hydrogenated nitrile rubber) is used instead of PIB.

[0109] Comparative Example 2

[0110] The difference from Example 11 is that in step S01, the PIB glue solution only contains the first polyisobutylene.

[0111] Comparative Example 3

[0112] The difference from Example 11 is that in step S01, the PIB glue solution only contains the second polyisobutylene.

[0113] Comparative Example 4

[0114] The difference from Example 4 is that in step S01, the PIB glue solution only contains the first polyisobutylene.

[0115] Comparative Example 5

[0116] The difference from Example 4 is that in step S01, the PIB glue solution only contains the second polyisobutylene.

[0117] The relevant parameters of the above Examples 1 to 16 and Comparative Examples 1 to 5 are recorded in Table 1.

[0118] Table 1

[0119]

[0120] The positive electrode sheets prepared in Examples 1 to 16 and Comparative Examples 1 to 5 were characterized as follows:

[0121] 1. Peel force test:

[0122] The pole piece is baked to fully remove the paraxylene solvent, and then rolled once to increase the density of the pole piece and improve the overall conductivity of the pole piece. During rolling, the roller gap is 20μm, the roller temperature is 45℃, and the roller speed is 3rpm.

[0123] The actual test method of peeling force is: cut the electrode into samples with a width of 30mm and a length of 250mm. Prepare a stainless steel plate, paste double-sided tape on one side of the stainless steel plate, fix one end of the prepared sample on the double-sided tape, and fix the other end on the chuck of the test peeling force equipment, and the peeling rate is 500mm / min. Take the data in the smooth area of ​​the test curve as the electrode peeling force, and the results are recorded in Table 2. The peeling force can reflect the bonding strength of the electrode. The greater the peeling force, the better the bonding performance of the adhesive.

[0124] Table 2

[0125] Group Pole peeling force N / mm Elastic deformation % Capacity retention rate % Example 1 5.73 6.9 65.32 Example 2 5.85 7.5 80.72 Example 3 5.96 7.7 91.13 Example 4 6.01 8.1 96.72 Example 5 5.87 7.7 90.6 Example 6 6.87 7.4 66.46 Example 7 6.89 7.9 83 Example 8 6.98 8.3 95.55 Example 9 6.99 8.5 97.99 Example 10 6.95 8.0 93.48 Embodiment 11 7.16 8.0 70.81 Example 12 7.2 8.4 88.01 Embodiment 13 7.31 8.9 97.7 Embodiment 14 7.58 9.3 99.02 Embodiment 15 7.07 7.5 66.6 Example 16 7.25 8.2 73.97 Comparative Example 1 5.54 5.9 51.02 Comparative Example 2 5.67 6.2 62.97 Comparative Example 3 5.69 6.4 64.76 Comparative Example 4 5.24 6.0 59.28 Comparative Example 5 5.7 6.7 65.02

[0126] 2. Elastic deformation test:

[0127] The pole piece is baked to fully remove the paraxylene solvent, and is rolled once to increase the density of the pole piece and improve the conductivity of the pole piece. During rolling, the roller gap is 20μm, the roller temperature is 45℃, and the roller speed is 3rpm.

[0128] The elastic deformation test method is: the pole piece is cut into 1.5cm×1.5cm samples, and the deformation of the powder material on the pole piece surface after rolling is tested on a nanoindenter. The indentation test uses a 1μm×1μm needle, a pressure of 10nN, and a vertical displacement of 5μm. The results are recorded in Table 2. The above elastic deformation can be used to reflect the ability of the pole piece to accommodate the volume change of the buffering active material. The larger the elastic deformation, the better the buffering performance of the binder.

[0129] 3. Electrochemical test:

[0130] The all-solid-state battery was subjected to electrochemical testing, and the test process was as follows: 30 cycles at 25°C, a cycle current of 0.33C, and a test voltage of 2.75V to 4.35V. The capacity retention rate was calculated by dividing the capacity after 30 cycles by the initial capacity, and the capacity retention rate after the cycle was obtained. The results are recorded in Table 2.

[0131] From the data in Table 2, we can see that:

[0132] Examples 1 to 4, Examples 6 to 8, and Examples 11 to 14 are respectively divided into three groups. Comparison of the examples within each group shows that: when the total mass content of the binder in the active material layer is the same, and the mass ratio of the first polyisobutylene to the second polyisobutylene in the binder is the same, as the viscosity-average molecular weight of the second polyisobutylene increases, the pole piece peeling force, elastic deformation degree, and capacity retention rate of the solid-state battery all increase. This is because as the viscosity-average molecular weight of the second polyisobutylene increases, the cohesive force of the second polyisobutylene increases, thereby increasing the viscosity of the binder to a certain extent, and the difficulty of forming a binder film increases, the binder is more likely to exist in the pole piece in the form of particles, and the elasticity of the binder will be better. In this way, during the cycle of the solid-state battery, the binder can buffer the stress caused by the volume expansion of the active material in the positive pole piece, thereby reducing the damage to the conductive network in the internal space of the positive pole piece, thereby increasing the capacity retention rate of the solid-state battery.

[0133] By comparing Example 1, Example 6 and Example 11, Example 2, Example 7 and Example 12, Example 3, Example 8 and Example 13, Example 4, Example 9 and Example 14 one by one, it can be seen that: when the total mass content of the binder in the active material layer is the same and the mass ratio of the first polyisobutylene to the second polyisobutylene in the binder is the same, as the viscosity-average molecular weight of the first polyisobutylene increases, the pole piece peeling force, elastic deformation degree and capacity retention rate of the solid-state battery all increase. This is because increasing the viscosity-average molecular weight of the first polyisobutylene can increase the cohesive force of the first polyisobutylene, thereby improving the viscosity of the binder to a certain extent, and increasing the difficulty of forming a binder film, the binder is more likely to exist in the pole piece in the form of particles, and the elasticity of the binder will be better. In this way, during the cycle of the solid-state battery, the binder can buffer the stress caused by the volume expansion of the active material in the positive pole piece, thereby reducing the damage to the conductive network in the internal space of the positive pole piece, thereby increasing the capacity retention rate of the solid-state battery.

[0134] This shows that when polyisobutylene with different viscosity average molecular weights is mixed, within a certain viscosity average molecular weight range, appropriately increasing the viscosity average molecular weight of polyisobutylene is beneficial to improving the viscosity of the binder and reducing its film-forming property, thereby improving the adhesion and deformation resistance of the pole piece. The adhesion of the pole piece surface directly affects the appearance and electrical properties of the pole piece surface. Too small adhesion will cause the active material layer and the current collector layer to separate, and even cause quality problems such as pole piece powder loss.

[0135] Comparing Example 4 with Example 5, Example 8 with Example 10, and Example 11 with Example 15, it can be seen that: when the total mass content of the binder in the active material layer is the same, and the viscosity average molecular weight of the first polyisobutylene is the same, and the viscosity average molecular weight of the second polyisobutylene is the same, the increase in the content of the first polyisobutylene in the binder will reduce the pole piece peeling force, elastic deformation, and capacity retention rate of the solid-state battery. This is because the increase in the content of the first polyisobutylene will reduce the viscosity of the binder and make it easy to form a film, so that the stress inside the positive pole piece cannot be well buffered, and it is easy to destroy the conductive network inside the positive electrode, thereby reducing the capacity retention rate. It shows that the mixing of polyisobutylenes with different viscosity average molecular weights and the appropriate introduction of more polyisobutylenes with large viscosity average molecular weights are conducive to improving the viscosity of the binder and reducing the film forming property, thereby providing a higher adhesion and buffer space for the pole piece, so as to achieve a higher capacity retention rate.

[0136] By comparing Example 11 and Example 16, it can be seen that as the total mass content of the binder in the active material layer increases, the pole piece peeling force, elastic deformation degree and capacity retention rate of the solid-state battery all increase.

[0137] Comparing Example 11 with Comparative Example 1, it can be seen that in Comparative Example 1, hydrogenated styrene butadiene rubber is used as a binder, and the total addition amount remains unchanged. Although the pole piece as a whole has a certain bonding force, the buffering capacity is low and an effective volume buffer zone cannot be formed, resulting in a large polarization, resulting in poor cycle stability.

[0138] Example 11 is compared with Comparative Example 2 and Comparative Example 3 respectively: Comparative Example 2 and Comparative Example 3 replace the compound binder with a single binder, and Comparative Example 2, which uses a smaller viscosity average molecular weight polyisobutylene, and Comparative Example 3, which uses a larger viscosity average molecular weight polyisobutylene, are inferior to Example 11 using a compound binder in terms of pole piece peeling force, elastic deformation, and capacity retention rate. Similarly, Example 4 is compared with Comparative Example 4 and Comparative Example 5 respectively: Comparative Example 4 and Comparative Example 5 replace the compound binder with a single binder, and Comparative Example 4, which uses a smaller viscosity average molecular weight polyisobutylene, and Comparative Example 5, which uses a larger viscosity average molecular weight polyisobutylene, are inferior to Example 4 using a compound binder in terms of pole piece peeling force, elastic deformation, and capacity retention rate. This is because polyisobutylene with the same viscosity average molecular weight has the same chain length, so it is not easy for the polymer molecular chains to fill each other's gaps and become entangled together, resulting in low viscosity. In addition, when the viscosity average molecular weight is small, the adhesive is easy to form a film, resulting in poor cushioning performance. When the viscosity average molecular weight is large, the elastic modulus increases, and the cushioning performance is also poor.

[0139] In summary, polyisobutylenes of different molecular weights can cooperate with each other, so that the resulting binder has better bonding and buffering capabilities. Moreover, polyisobutylenes of different molecular weights can also work synergistically to make it difficult for the binder to form a film in the electrode, so that the binder is more spherical in shape inside the electrode. These spherical binders can effectively relieve stress, thereby improving the cycle performance of solid-state batteries.

[0140] The volume of the electrode material changes during charging and discharging; when only solid electrolyte exists inside the pole piece, the transmission of lithium ions can only be achieved through the solid-solid contact between the electrode material and the solid electrolyte. The volume change of the above-mentioned electrode material will cause poor solid-solid contact inside the pole piece, hindering the transmission of lithium ions. The present application introduces a compounded adhesive with good elasticity and strain resistance, which can buffer the volume change of the material inside the pole piece, achieve stable lithium ion transmission, and improve the cycle performance of the solid-state battery.

[0141] The embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method and core idea of ​​the present application. At the same time, for technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A solid-state battery, characterized in that: The invention comprises an electrode, wherein the electrode comprises a current collector and an active material layer combined with the current collector, wherein the active material layer comprises an active material and a binder, wherein the binder comprises polyisobutylene, and the polyisobutylene comprises a first polyisobutylene and a second polyisobutylene, wherein the viscosity average molecular weight of the first polyisobutylene is less than the viscosity average molecular weight of the second polyisobutylene.

2. The solid-state battery according to claim 1, characterized in that: The viscosity average molecular weight of the polyisobutylene is 40,000 to 2,600,000.

3. The solid-state battery according to claim 2, characterized in that: The viscosity average molecular weight of the first polyisobutylene is 40,000 to 85,000, and the viscosity average molecular weight of the second polyisobutylene is 425,000 to 2,600,000.

4. The solid-state battery according to claim 2, characterized in that: The difference between the viscosity average molecular weight of the second polyisobutylene and the viscosity average molecular weight of the first polyisobutylene is greater than or equal to 340,000.

5. The solid-state battery according to claim 2, characterized in that: The ratio of the viscosity average molecular weight of the second polyisobutylene to the viscosity average molecular weight of the first polyisobutylene is 5-65.

6. The solid-state battery according to claim 1, characterized in that: In the binder, the content of the first polyisobutylene is 30 wt % to 80 wt %, and the content of the second polyisobutylene is 20 wt % to 70 wt %.

7. The solid-state battery according to claim 1, characterized in that: In the active material layer, the content of the binder is 0.5 wt % to 5 wt %.

8. The solid-state battery according to claim 1, characterized in that: The active material layer also includes a solid electrolyte.

9. The solid-state battery according to claim 8, characterized in that: In the active material layer, the content of the active material is 70 wt% to 94 wt%, or the content of the conductive agent is 0.5 wt% to 5 wt%, or the content of the solid electrolyte is 5 wt% to 20 wt%.

10. The solid-state battery according to claim 8, characterized in that: The solid electrolyte includes at least one of a sulfide electrolyte, a halide electrolyte, an oxide electrolyte and a polymer electrolyte.

11. The solid-state battery according to claim 1, characterized in that: The active material includes at least one of a positive electrode active material and a negative electrode active material, the positive electrode active material includes at least one of lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium manganese iron phosphate and a lithium-rich manganese-based positive electrode material; and / or the negative electrode active material includes at least one of graphite, silicon, silicon carbon and lithium titanate.

12. The solid-state battery according to claim 1, characterized in that: The active material layer further includes a conductive agent, and the conductive agent includes at least one of carbon black, conductive graphite, carbon nanotubes, and nano-carbon fibers.